The (Hidden) Financial Flows of Terrorist and Transnational Crime Organizations: A Literature Review and Some Preliminary Empirical Results - Friedrich Schneider
The financial means of international terror and transnational organized crime organizations are analyzed. First, some short remarks about the organization of international terror organizations are made. Second and in a much more detailed way a literature review is provided about the financing of terrorist and transnational organized crime organizations, their sources and the various methods they use. Third, an attempt is made to estimate the financial means of terror organizations with the help of a latent estimation approach (MIMIC procedure). The figures show that Al Qaeda and other terror organizations have sufficient financial means. Fourth, some remarks are made about the negative effects of terror on the economy in highly developed countries and some strategies are presented to combat (the financing) of terrorism.Financial flows of terrorist organizations, financial flows of transnational organized crime, Hawala banking, money laundering, transnational organized crime, terrorist organizations, kinds of terrorist financing